2006
DOI: 10.1111/j.1398-9995.2006.01011.x
|View full text |Cite
|
Sign up to set email alerts
|

Twelve‐year follow‐up after discontinuation of preseasonal grass pollen immunotherapy in childhood

Abstract: This prospective controlled prolonged follow-up study demonstrates the ongoing clinical benefit 12 years after discontinuation of SIT. Furthermore, the reduction in onset of new sensitization, which was found 6 years after discontinuation of SIT, is sustained 6 years later.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
191
0
5

Year Published

2007
2007
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 247 publications
(201 citation statements)
references
References 13 publications
5
191
0
5
Order By: Relevance
“…27 Efficacy evaluation (symptoms and rescue medication intake) was done 6 and 12 years after stopping SIT. This group was compared with a nondesensitized control group.…”
Section: Indications and Contraindicationsmentioning
confidence: 99%
“…27 Efficacy evaluation (symptoms and rescue medication intake) was done 6 and 12 years after stopping SIT. This group was compared with a nondesensitized control group.…”
Section: Indications and Contraindicationsmentioning
confidence: 99%
“…Eng ve ark. (17,18), üç yıl üst üste mevsim öncesi immunoterapi yapılan çocuklarda tedavinin bitiminden altı yıl ve 12 yıl sonra bile kontrol grubuyla karşılaştırıldı-ğında anlamlı klinik etkinlik görüldüğünü bildirmişlerdir.…”
Section: Discussionunclassified
“…Table 1 shows descriptive data for the 18 systematically reviewed studies (20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35)(36)(37). [11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30] and seven adult studies (31-37) included a total of 11 106 patients (1049 children, 10 057 adults), of which 8369 (75.6%) were included only in the Purello D'Ambrosio study (31). Nine of 18 studies were conducted in Italy (21,22,24,25,29,31,(33)(34)(35), four in Turkey, and (26)…”
Section: Resultsmentioning
confidence: 99%
“…Our search strategy identified 1378 unique publications, including over 338 peer-reviewed studies published from inception to June 30, 2015 finally retrieved , of which 18 met the inclusion criteria (20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35)(36)(37). We excluded the Jacobsen study (38), because the outcome was reported in a subgroup of patients regardless of the treatment received, the Eifan (39) Acquistapace (40), Szepfalusi (41), and Shao (42) studies because they were not long-term studies (<3 years of treatment/follow-up).…”
Section: Resultsmentioning
confidence: 99%